2012
DOI: 10.1097/inf.0b013e31822f8a92
|View full text |Cite
|
Sign up to set email alerts
|

β-lactam Resistance, Serotype Distribution, and Genotypes of Meningitis-causing Streptococcus pneumoniae, Rio de Janeiro, Brazil

Abstract: Background Here, we report a laboratory-based study of Streptococcus pneumoniae recovered from patients with meningitis in Rio de Janeiro State, Brazil. Methods The aim of this study was to determine the evolution of β-lactam resistance, antimicrobial susceptibility pattern, serotypes, and genetic diversity of S. pneumoniae, isolated from meningitis patients between 2000 and 2008. Results A total of 264 S. pneumoniae recovered from patients between 2000 and 2008 were included. Susceptibility testing (E-tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 26 publications
2
25
0
3
Order By: Relevance
“…1). Most of the 16 different capsular types (1, 6A, 6B, 6C, 9N, 10A, 11A, 12F, 13, 14, 15C, 16F, 18C, 19A, 23A, and 23F) observed among the isolates included in the present study corresponded to types commonly found in our region (30,31), reinforcing the concept that serotype distribution among Opt r S. pneumoniae strains is mostly dependent on the epidemiological profile of each area (2,3,10,11,12). Identical serotypes were observed for the Opt r and Opt s subpopulations derived from the same culture.…”
Section: Resultsmentioning
confidence: 69%
“…1). Most of the 16 different capsular types (1, 6A, 6B, 6C, 9N, 10A, 11A, 12F, 13, 14, 15C, 16F, 18C, 19A, 23A, and 23F) observed among the isolates included in the present study corresponded to types commonly found in our region (30,31), reinforcing the concept that serotype distribution among Opt r S. pneumoniae strains is mostly dependent on the epidemiological profile of each area (2,3,10,11,12). Identical serotypes were observed for the Opt r and Opt s subpopulations derived from the same culture.…”
Section: Resultsmentioning
confidence: 69%
“…S.pneumoniae serotiplerinin tedavi süreçlerine karşı direnç geliştirmesi güncel bir sorundur. Bu durumda, antibiyotik tedavisinin yanında, aspleni ile oluşan immün yetmezliğin düzeltilmesi gerekebilir 6 . Beta-D-glukan (BDG), mantarlarda, mayada ve kepekte bulunan dallanmış bir glukoz polimeridir.…”
Section: Introductionunclassified
“…Streptococcus pneumoniae, Haemophilus in luenzae and Neisseria meningitidis are the most common encapsulated microorganisms that have been found to be responsible for sepsis after splenectomy [19][20][21][22][23]. In blood culture of many patients with suspected sepsis, gram positive bacterium Streptococcus pneumoniae has been isolated in 50-90% of the time [23,25]. Yet the another retrospective study, in 66% of the cases pneumococcus were responsible for sepsis after splenectomy [25].…”
Section: Paliative Radiation Therapy To Spleenmentioning
confidence: 99%
“…It is mostly seen in the irst two years after splenectomy and have high mortality rate of between 50-60% [4,5,13,[16][17][18]. Streptococcus pneumoniae, Haemophilus in luenzae and Neisseria meningitidis are the most common encapsulated microorganisms that have been found to be responsible for sepsis after splenectomy [19][20][21][22][23]. In blood culture of many patients with suspected sepsis, gram positive bacterium Streptococcus pneumoniae has been isolated in 50-90% of the time [23,25].…”
Section: Paliative Radiation Therapy To Spleenmentioning
confidence: 99%
See 1 more Smart Citation